Lanskap Linguistik di Pondok Modern Darussalam Gontor Ponorogo Kajian: Pola, Fungsi, dan Refleksinya Bagi Lingkungan Bahasa - Aziz, Umar Abdul; Arifa, Zakiya; Ibrahim, Faisal Mahmoud Adam (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
Along with the growing popularity of digital technology in language learning, Pondok Modern Darussalam Gontor actually proves that the boards, and writings around the physical environment can be effective 'silent teachers' in the formation of a language environment.. This study aims to determine the role of the linguistic landscape as a means of forming a language environment. This research uses a qualitative approach with descriptive methods to describe the form, pattern, function and reflection of the relationship between the linguistic landscape and the applied language environment. Data were collected by means of observation and documentation, in which various writing signs or signboards found in the cottage environment will be noted and collected. Then the researcher photographed the writing signs in the cottage environment as visual data with a cellphone camera. The focus of this research is the writing sign or signboard located in the dormitory building, cottage building and classroom which amounted to 208 linguistic landscape objects. The result of this research is that PMDG Gontor applies a diverse form of linguistic landscape, including monolingual, bilingual, and multilingual patterns. The objects are also analyzed based on two main functions, namely informative function and symbolic function. Then the linguistic landscape has a significant role from both psychological, linguistic and pedagogical aspects